2008
DOI: 10.1002/ppul.20823
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and clinical impact of pulmonary artery sling on school‐aged children: A large‐scale screening study

Abstract: This is the first study to determine the prevalence of PAS as 59 per million school-aged children by a large-scale screening using 2DE. Although the majority of children with PAS have associated TBA and impaired pulmonary function, all patients with PAS were unrecognized due to non-specific symptoms. Early identification of PAS and surgery result in significant improvement in pulmonary function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 26 publications
0
45
0
7
Order By: Relevance
“…23 This would make pulmonary artery sling more common in MWS patients, and we can therefore consider it a sign that may lead us to suspect MWS.…”
Section: Discussionmentioning
confidence: 99%
“…23 This would make pulmonary artery sling more common in MWS patients, and we can therefore consider it a sign that may lead us to suspect MWS.…”
Section: Discussionmentioning
confidence: 99%
“…These patients present with significant airway obstruction and biphasic stridor, or with difficulty at intubation for another procedure. This abnormality frequently occurs concomitantly with congenital cardiovascular defects, particularly pulmonary artery slings, 67 can vary from a single complete ring to a segment that is the length of the trachea, and can include bronchial cartilage rings. Over the decades many procedures were used for treatment, with limited success and high mortality.…”
Section: Complete Tracheal Ringsmentioning
confidence: 98%
“…2,3,5,6 Likewise our patient, the male sex was predominant in many studies such as the series of Yu and Gikonyo who reported 72% and 60% of male patients respectively. 2,5 Although there are 3 theories to explain this vascular malformation, none is unanimous. The first one state it is a total absence of development of the LPA and the blood supply comes from the RPA.…”
Section: Discussionmentioning
confidence: 88%
“…The respiratory signs are not specific and may include wheezing, stridor, dyspnea on effort, coughing and recurrent infections of lower airways. 2 In ideal situation, 3 the diagnosis is made by echocardiogram while the bronchoscopy accesses the bronchial stenosis. The treatment is strictly surgical and classically consists of cutting the LPA then reimplanting it on the pulmonary artery (PA) main stem by sternotomy and cardiopulmonary bypass (CPB).…”
mentioning
confidence: 99%